Distinct effect of impact rise times on immediate and early neuropathology after brain injury in juvenile rats. Issue 10 (5th May 2014) - Neuberger, Eric J.; Abdul Wahab, Radia; Jayakumar, Archana; Pfister, Bryan J.; Santhakumar, Vijayalakshmi
<x xml:space="preserve">Abstract</x> Traumatic brain injury (TBI) can occur from physical trauma from a wide spectrum of insults ranging from explosions to falls. The biomechanics of the trauma can vary in key features, including the rate and magnitude of the insult. Although the effect of peak injury pressure on neurological outcome has been examined in the fluid percussion injury (FPI) model, it is unknown whether differences in rate of rise of the injury waveform modify cellular and physiological changes after TBI. Using a programmable FPI device, we examined juvenile rats subjected to a constant peak pressure at two rates of injury: a standard FPI rate of rise and a faster rate of rise to the same peak pressure. Immediate postinjury assessment identified fewer seizures and relatively brief loss of consciousness after fast‐rise injuries than after standard‐rise injuries at similar peak pressures. Compared with rats injured at standard rise, fewer silver‐stained injured neuronal profiles and degenerating hilar neurons were observed 4–6 hr after fast‐rise FPI. However, 1 week postinjury, both fast‐ and standard‐rise FPI resulted in hilar cell loss and enhanced perforant path‐evoked granule cell field excitability compared with sham controls. Notably, the extent of neuronal loss and increase in dentate excitability were not different between rats injured at fast and standard rates of rise to peak pressure. Our data indicate that reduced cellular damage and improved immediate neurological outcome after fast rising primary concussive injuries mask the severity of the subsequent cellular and neurophysiological pathology and may be unreliable as a predictor of prognosis. © 2014 Wiley Periodicals, Inc.